Tantangan Perceraian Sipil Bagi Perkawinan Katolik: Antara Hukum Ilahi Dan Hukum Manusia - Yohanes Servatius Lon (Jurnal Selat, 2020)
Marriage is both as a sacred/divine and social thing. Therefore marriage is part of worship as well as being bound to legal and social aspects. Then marriage is regulated both by a religious and by non-religious institution. This paper explores the different principles regarding divorce of a legal marriage according to Catholic and civil law. Marriage in Catholic law is eternal and there is no principle of divorce. Whereas civil law allows couple to divorce. Catholics' marriages that are legal according to Catholic Church law but divorced by a State Court judge have created many new problems. This study aims to explore the complexity of the challenges facing the Catholic couples. The method of this research is a qualitative. Using a library approach and field study, this study found that there were legal uncertainties and injustices experienced by Catholic couples who were divorced by a state court. This study recommends that there is a need for synergy between state courts and church courts in marital divorce matters. Furthermore, it requires state law that truly respects the autonomy of religious law.